The catastrophic out-of-pocket health expenditure of multiple sclerosis patients in Iran - Farid Gharibi; Ali Imani; Koustuv Dalal (BMC, 2021)
Abstract Background The present study was designed and conducted to evaluate multiple sclerosis (MS) treatment costs and the resulting economic impact imposed on MS patients in Iran. Methods This was a cross-sectional study, among randomly selected 300 MS patients, registered in the MS Association of East Azerbaijan Province, Iran (1 year after their treatment began). The regression analysis, ANOVA, T-test, and chi-square were used. Results The average amount of out-of-pocket payments (OOPs) by MS patients during the previous year was 1669.20 USD, most of which was spent on medication, rehabilitation care, and physician visits. Their mean annual income was 5182.84 USD. Fifty four percent of families with an MS patient suffer from catastrophic health expenditure (CHE) and 44% experience poverty caused by the OOPs. Occupational status, having supplemental health insurance, and being residents of Tabriz significantly affect OOPs, CHE, and the resulting poverty (P < 0.05). Conclusion The catastrophic financial burden of health care costs on MS patients and their families justifies health policymakers to promote pre-payment systems and provide subsidies to less well-off patients to protect them from the unfairness of OOPs and its resulting CHE and poverty.